Septins of Platyhelminths: identification, phylogeny, expression and localization among developmental stages of Schistosoma mansoni. - Ana E Zeraik; Gabriel Rinaldi; Victoria H Mann; Anastas Popratiloff; Ana P U Araujo; Ricardo Demarco; Paul J Brindley (Public Library of Science (PLoS), 2013)
Septins are a family of eukaryotic GTP binding proteins conserved from yeasts to humans. Originally identified in mutants of budding yeast, septins participate in diverse cellular functions including cytokinesis, organization of actin networks, cell polarity, vesicle trafficking and many others. Septins assemble into heteroligomers to form filaments and rings. Here, four septins of Schistosoma mansoni are described, which appear to be conserved within the phylum Platyhelminthes. These orthologues were related to the SEPT5, SEPT10 and SEPT7 septins of humans, and hence we have termed the schistosome septins SmSEPT5, SmSEPT10, SmSEPT7.1 and SmSEPT7.2. Septin transcripts were detected throughout the developmental cycle of the schistosome and a similar expression profile was observed for septins in the stages examined, consistent with concerted production of these proteins to form heterocomplexes. Immunolocalization analyses undertaken with antibodies specific for SmSEPT5 and SmSEPT10 revealed a broad tissue distribution of septins in the schistosomulum and colocalization of septin and actin in the longitudinal and circular muscles of the sporocyst. Ciliated epidermal plates of the miracidium were rich in septins. Expression levels for these septins were elevated in germ cells in the miracidium and sporocyst. Intriguingly, septins colocalize with the protonephridial system of the cercaria, which extends laterally along the length of this larval stage. Together, the findings revealed that schistosomes expressed several septins which likely form filaments within the cells, as in other eukaryotes. Identification and localization demonstrating a broad distribution of septins across organs and tissues of schistosome contributes towards the understanding of septins in schistosomes and other flatworms.